Lignin-based porous carbon for supercapacitor and preparation method of lignin-based porous carbon
By using potassium carbonate and potassium dihydrogen citrate as activators, lignin is directly carbonized and activated lignin is prepared in one step, which solves the template residue, complex operation and environmental protection problems in the prior art, and realizes efficient and environmentally friendly preparation of supercapacitor electrode materials.
Patent Information
- Application Number
- CN202411770611.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, when preparing lignin-based porous carbon for supercapacitors, there are template residue problems, complex and time-consuming operations, and the template agent used is expensive, and the chemicals used during the preparation process are harmful to the human body.
Porous carbon was prepared by combining two green and cheap activators, potassium carbonate and potassium dihydrogen citrate as activators and supplementary carbon sources, and electrodes with excellent capacity and rate performance were prepared using lignin-based porous carbon.
It realizes efficient preparation of lignin-based porous carbon without using template agents, solves the problems of environmental pollution and resource waste, and improves the electrochemical performance and cycle stability of supercapacitors.
Smart Images

Figure CN119581238A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a lignin-based porous carbon for a supercapacitor and a preparation method thereof, belonging to the technical field of electrode materials. Background Art
[0002] The energy crisis and climate change issues brought about by the rapid development of human industrial society have become the focus of attention of countries around the world. Under the background of "dual carbon", the development and utilization of new energy and low-carbon technologies have become a top priority. Electrochemical energy storage technology is one of the main forms of new green energy storage and has great development potential. In recent years, research on large-capacity electrochemical energy storage systems has continued to expand.
[0003] Electrochemical energy storage devices play a very important role in the development of green and sustainable energy storage and conversion technology. Supercapacitors are energy storage devices between traditional physical capacitors and secondary batteries. Their high power density, fast charge and discharge, long cycle life and wide applicable temperature range have attracted widespread attention in portable electronic devices, electric vehicles and transportation.
[0004] Porous carbon materials have many advantages in supercapacitors, such as 1. High specific surface area, which provides more active sites for charge storage; 2. Adjustable pore structure, the pore structure of porous carbon can be adjusted to adapt to different electrolyte ions and optimize charge storage and transmission; 3. The optimization of pore size distribution can ensure the rapid diffusion and transmission of electrolyte ions at high current density, and improve the specific surface area utilization of electrode materials; 4. Excellent conductivity, porous carbon materials have good conductivity, which is crucial to improving the charging and discharging efficiency of supercapacitors. Excellent conductivity helps to increase the reaction rate of the electrode, thereby improving the power density of supercapacitors; 5. Physical and chemical stability, porous carbon materials have good physicochemical stability, which means that they have a long service life and good cycle stability in electrochemical environments; 6. Low cost and environmental protection, porous carbon materials are usually derived from a wide range of low-cost precursors, such as biomass, asphalt, etc., which can be mass-produced and are environmentally friendly.
[0005] A variety of methods are used in the prior art to prepare porous carbon materials. For example, patent CN115346801B uses alkaline soluble calcium salt as a template, lignin as a carbon source, and alkali metal hydroxide as a co-solvent to prepare lignin-derived porous carbon for supercapacitors. However, when dual templates are used to prepare porous carbon materials, there is often a problem of template residue, and the operation process is complicated and time-consuming.
[0006] Patent CN106744793B mixes the crude purified alkali lignin from papermaking black liquor with the triblock polymer Pluronic F127 and Mg(CH3COO)2·4H2O to prepare porous carbon materials for alkali lignin-based supercapacitors, which pays more attention to resource recycling. However, the template polymer Pluronic F127 used is expensive, and the large-scale use cost is relatively high. In addition, drugs such as tetrahydrofuran and formaldehyde are used in the preparation process, which are harmful to the human body.
[0007] Reference 1 (Preparation of porous carbon materials using potassium citrate as carbon precursor and study of their electrochemical properties) uses potassium citrate and bacterial cellulose as mixed carbon precursors to prepare a three-dimensional layered porous carbon material with overlapping fiber networks and porous sheets. Although bacterial cellulose has excellent performance, its production cost is high, its yield is low, and its economic efficiency is poor when used on a large scale; compared with lignin, its structure is relatively simple and lacks the complex aromatic structure of lignin, which limits its performance in certain applications.
[0008] Lignin, as the second most abundant biomass material in nature, is often treated as waste in the papermaking industry, which not only pollutes the environment but also wastes resources. However, its carbon content is as high as 60%, making it an ideal natural polymer carbon material. Therefore, how to make full use of lignin and prepare lignin-based porous carbon materials without using templates, effectively solve environmental problems, and realize the high added value recycling of industrial lignin, is an urgent problem to be solved. Summary of the invention
[0009] In order to solve the above problems, the present invention uses a combination of two green and cheap activators, potassium carbonate as a green activator, and potassium dihydrogen citrate as a green activator and a supplementary carbon source, to directly carbonize and activate lignin in one step to obtain porous carbon, and then use the lignin-based porous carbon to prepare electrodes with excellent capacity and rate performance. On this basis, supercapacitors are further prepared. While being environmentally friendly, the prepared material has good electrochemical properties.
[0010] The first object of the present invention is to provide a method for preparing lignin-based porous carbon, wherein the method comprises mixing enzymatically hydrolyzed lignin, potassium carbonate and potassium dihydrogen citrate in a mass ratio of 1:(1.75-4.375):(0.25-0.625), carbonizing, cooling, washing and drying to obtain lignin-based porous carbon.
[0011] In one embodiment, the mass ratio of enzymatically hydrolyzed lignin, potassium carbonate and potassium dihydrogen citrate is preferably 1:(1.75-3.5):(0.25-0.5), and more preferably 1:2.625:0.375.
[0012] In one embodiment, the carbonization temperature is 600-900°C, preferably 600-700°C, and more preferably 700°C.
[0013] In one embodiment, a method for preparing lignin-based porous carbon comprises the following steps:
[0014] Enzymatically hydrolyzed lignin, potassium carbonate and potassium dihydrogen citrate are mixed in a mass ratio of 1:(1.75-4.375):(0.25-0.625), carbonized at 600-900°C for 1-3h, and then taken out after cooling to below 60°C, washed and dried to obtain lignin-based porous carbon.
[0015] In one embodiment, the carbonization is to introduce nitrogen protective gas at a rate of 90 to 110 mL / min, increase the temperature in the tube furnace to 600 to 900° C. at a heating rate of 4 to 6° C. / min, and then carbonize at 600 to 900° C. for 1 to 3 hours.
[0016] In one embodiment, the washing is to wash the carbonized product with 1M HCl to remove all inorganic salts, then wash with excess deionized water until the pH is 7, and filter.
[0017] In one embodiment, the drying is to place the filter residue in an oven at 90-110° C. and dry it for 10-15 hours.
[0018] In one embodiment, the method for preparing lignin-based porous carbon further comprises the following steps:
[0019] The enzymatic lignin, potassium carbonate and potassium dihydrogen citrate are mixed in a mass ratio of 1: (1.75-4.375): (0.25-0.625), and the mixture is fully ground and placed in a tube furnace. A nitrogen protective gas is introduced at a rate of 90-110 mL / min, and the temperature in the tube furnace is increased to 600-900° C. at a heating rate of 4-6° C. / min. The mixture is carbonized at 600-900° C. for 1-3 hours, and then naturally cooled to room temperature. The carbonized product is repeatedly washed with 1M HCl and deionized water until the pH is neutral. Finally, the mixture is placed in an oven and dried at 90-110° C. for 10-15 hours to obtain lignin-based porous carbon.
[0020] The second object of the present invention is to provide a lignin-based porous carbon prepared by the above method.
[0021] The third object of the present invention is to provide a method for improving the specific surface area, pore size distribution, carbon yield and electrochemical performance of lignin-based porous carbon, characterized in that the method is to mix enzymatic lignin, potassium carbonate and potassium dihydrogen citrate in a mass ratio of 1: (1.75-4.375): (0.25-0.625), carbonize, cool, wash and dry to obtain lignin-based porous carbon.
[0022] In one embodiment, the method comprises the steps of:
[0023] Enzymatically hydrolyzed lignin, potassium carbonate and potassium dihydrogen citrate are mixed in a mass ratio of 1:(1.75-4.375):(0.25-0.625), carbonized at 600-900°C for 1-3h, and then taken out after cooling to below 60°C, washed and dried to obtain lignin-based porous carbon.
[0024] The fourth object of the present invention is to provide an application of the lignin-based porous carbon of the present invention or the above method in preparing a working electrode.
[0025] In one embodiment, the working electrode is prepared by mixing the lignin-based porous carbon prepared above with a binder and a conductive agent, rolling, and drying.
[0026] In one embodiment, the binder includes but is not limited to polytetrafluoroethylene and polyvinylidene fluoride; the conductive agent includes but is not limited to acetylene black, carbon fiber, and carbon nanotubes.
[0027] In one embodiment, the working electrode is prepared by mixing the above-prepared lignin-based porous carbon with a binder and a conductive agent in a mass ratio of (7.5-8.5):(0.5-1):(0.5-2), rolling and drying.
[0028] In one embodiment, the method for preparing the working electrode comprises the following steps:
[0029] The dried porous carbon, binder (polytetrafluoroethylene) and conductive agent (acetylene black) are ultrasonically mixed in 10-20 mL of anhydrous ethanol in a mass ratio of 8:1:1 for 10-30 minutes. After the ethanol evaporates, the slurry is rolled into a film, and the film is placed in a vacuum oven at 60-80°C and dried for 20-25 hours to remove moisture and organic solvents. The dried film is cut into 1 cm×1 cm squares, weighed and recorded, and then pressed onto a clean nickel foam using a tablet press at a pressure of 5-20 MPa to obtain a lignin-based porous carbon working electrode for a supercapacitor.
[0030] A fifth object of the present invention is to provide an application of the lignin-based porous carbon of the present invention or the above method in preparing a supercapacitor.
[0031] In one embodiment, the supercapacitor is obtained by assembling the working electrode, diaphragm and spring prepared as above.
[0032] In one embodiment, the supercapacitor is obtained by assembling the working electrode, diaphragm, and spring fragment prepared above, placing them into a supercapacitor housing, injecting electrolyte, and then encapsulating the housing.
[0033] In one embodiment, the electrolyte includes but is not limited to potassium hydroxide solution, sodium sulfate solution, and propylene carbonate organic solution.
[0034] In one embodiment, the method for preparing the supercapacitor comprises the following steps:
[0035] The working electrode prepared above is cut into sheets to obtain electrode sheets with a mass of 2 to 6 mg as positive and negative electrodes. The positive electrode, diaphragm, negative electrode and spring are stacked and assembled in sequence, loaded into a supercapacitor casing, the electrolyte is injected, and the casing is packaged and formed.
[0036] Beneficial Effects
[0037] (1) The present invention utilizes a simple green composite activator to carbonize and activate lignin in one step, potassium carbonate is used as a green activator, potassium dihydrogen citrate is used as a green activator and a supplementary carbon source, and after obtaining the carbon material, the prepared electrode has excellent capacity and rate performance, thereby achieving the purpose of improving the energy density and power density of the supercapacitor electrode;
[0038] (2) The present invention utilizes biowaste lignin in a high-value manner to prepare porous carbon, thereby solving the problems of poor conductivity and low carbon yield of amorphous carbon materials in the current preparation of supercapacitor electrodes, and improving the effective unit capacity and rate performance of supercapacitor devices;
[0039] (3) The lignin-based porous carbon prepared by the present invention has excellent electrochemical properties. In the three-electrode test (the electrolyte is 6M KOH), the current density is 1A / g and the specific capacitance can reach up to 310F / g. The lignin-derived porous carbon material is assembled with 6M KOH electrolyte and diaphragm material into a symmetrical supercapacitor. After 10,000 cycles of charge and discharge at 5A / g, the specific capacitance of the capacitor decays slightly, the capacitance retention rate is as high as 99.5%, and the coulombic efficiency is close to 100%, and the cycle stability is very excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1The scanning electron microscope images of the lignin-based porous carbons obtained in Examples 1 and 2, wherein (a) is the lignin-based porous carbon obtained in Example 2 by enzymatically hydrolyzing lignin, potassium carbonate and potassium dihydrogen citrate in a mass ratio of 1:1.75:0.25; (b) is the lignin-based porous carbon obtained in Example 1 by enzymatically hydrolyzing lignin, potassium carbonate and potassium dihydrogen citrate in a mass ratio of 1:2.625:0.375; (c) is the lignin-based porous carbon obtained in Example 2 by enzymatically hydrolyzing lignin, potassium carbonate and potassium dihydrogen citrate in a mass ratio of 1:3.5:0.5; (d) is the lignin-based porous carbon obtained in Example 2 by enzymatically hydrolyzing lignin, potassium carbonate and potassium dihydrogen citrate in a mass ratio of 1:4.375:0.625.
[0041] Figure 2 The nitrogen adsorption / desorption curves and pore size distribution diagrams of the lignin-based porous carbons obtained in Examples 1 and 2 are shown in Figures 1 and 2, wherein (a) is the nitrogen adsorption / desorption diagram; and (b) is the pore size distribution diagram.
[0042] Figure 3 The three-electrode electrochemical performance diagrams of the lignin-based porous carbon obtained in Examples 1 and 2, wherein (a) is a cyclic voltammetry (CV) curve; (b) is a constant current charge and discharge (GCD) curve; and (c) is an impedance EIS curve.
[0043] Figure 4 These are the electrochemical performance diagrams of the supercapacitor device assembled with the lignin-based porous carbon obtained in Example 1, where (a) is the cyclic voltammetry (CV) curve at 5 mV / s, 20 mV / s, 50 mV / s, and 100 mV / s; (b) is the constant current charge and discharge (GCD) curve at current densities of 1 A / g, 2 A / g, 5 A / g, 10 A / g, and 20 A / g, respectively; (c) is the impedance EIS curve; and (d) is the 10,000 cycle stability at 5 A / g.
[0044] Figure 5 The three-electrode test electrochemical performance diagram of the lignin-based porous carbon obtained in Example 3, wherein (a) is a cyclic voltammetry (CV) curve; (b) is a constant current charge-discharge (GCD) curve; (c) is an impedance EIS curve; in the legend, LPC-4-600, LPC-4-700, LPC-4-800, and LPC-4-900 respectively represent the lignin-based porous carbon obtained by carbonization at 600°C, 700°C, 800°C, and 900°C when the mass ratio of lignin to composite activator is 1:4 (potassium carbonate: potassium dihydrogen citrate = 3.5:0.5). DETAILED DESCRIPTION
[0045] 1. The detection / calculation methods involved in the following embodiments and comparative examples:
[0046] (1) Specific surface area and pore size distribution
[0047] The specific surface area and pore size distribution curve of the sample were obtained by nitrogen adsorption-desorption curve on Micromeritics ASAP2460 adsorption instrument, the operating temperature was -196 ° C (liquid nitrogen temperature), and the sample was dehydrated at 200 ° C under nitrogen protection before testing. The specific surface area (SSA) of the sample was calculated by the Brunauer-Emmett-Teller (BET) method, and the pore size distribution curve (PSD) of the sample was obtained by the density functional theory model (DFT). The specific surface area was calculated by the BET method, referring to the following calculation formula:
[0048] Specific surface area (S) = N A ·A m / W·V m
[0049] Among them, N A is the Avogadro constant, A m is the cross-sectional area of the adsorbed gas molecules, W is the mass of the sample being tested, and Vm is the volume of gas required to fully cover the catalyst surface with the first layer.
[0050] (2) Calculation of carbon yield
[0051] The carbon yield was calculated by the formula: (the mass of the lignin-based porous carbon finally obtained / the mass of the enzymatically hydrolyzed lignin added)×100%.
[0052] (3) Three-electrode system electrochemical test
[0053] The prepared lignin-based porous carbon, conductive agent acetylene black, and binder PTFE (polytetrafluoroethylene) were ultrasonically mixed in 10 mL of anhydrous ethanol in a mass ratio of 8:1:1 for 20 minutes. After the ethanol evaporated, the slurry was rolled into a film, and the film was placed in a vacuum oven at 80°C and dried for 24 hours to remove moisture and organic solvents. The dried film was cut into 1 cm×1 cm squares, weighed and recorded, and then pressed onto the washed nickel foam using a tablet press at a pressure of 10 MPa to obtain a lignin-based porous carbon working electrode for supercapacitors.
[0054] Hg / HgO was used as the reference electrode and platinum sheet was used as the auxiliary electrode (1×1 cm 2 ), 6M KOH as the electrolyte, and then cyclic voltammetry test, constant current charge and discharge test, and AC impedance test were carried out on a Cost electrochemical tester.
[0055] (4) Two-electrode system electrochemical test
[0056] Prepare the working electrode in the manner described in (2) above, take two sheets of equal mass as the positive and negative electrodes, stack the positive electrode, diaphragm, negative electrode and spring in sequence, assemble them, put them into the supercapacitor casing, inject 6 mol / L potassium hydroxide solution, and then package the casing and form it at a pressure of 10 MPa.
[0057] After standing at room temperature for 2 hours, cyclic voltammetry test, constant current charge and discharge test and AC impedance test were performed on the Coster electrochemical tester.
[0058] In the three-electrode system, the mass specific capacitance is calculated according to the following formula:
[0059]
[0060] In a two-electrode system, the mass specific capacitance is calculated according to the following formula:
[0061]
[0062] Where C g is the mass specific capacitance (F / g), I is the current density (A), Δt is the discharge time (s), m is the mass of active material in a single electrode (g), and ΔV is the change in the operating voltage window (V).
[0063] Calculation of energy density and power density:
[0064]
[0065] Where E is energy density (Wh / kg), P is power density (W / kg), ΔV is the change in operating voltage window (V), and Δt is the discharge time (s).
[0066] 2. Raw materials in the following examples and comparative examples:
[0067] Potassium carbonate, potassium dihydrogen citrate, potassium citrate, potassium hydroxide, and hydrochloric acid were all of analytical grade and purchased from Sinopharm Chemical Reagent Co., Ltd.
[0068] Enzymatic lignin refers to a lignin preparation obtained by removing sugars (carbohydrates) from plant raw materials after enzymatic hydrolysis. The enzymatic lignin used in the present invention can be any lignin separated from the residue of enzymatically hydrolyzing biomass raw materials to prepare energy. In the embodiments and comparative examples, the enzymatic lignin in the production waste of enzymatically hydrolyzing biomass raw materials to prepare energy is specifically provided by Guotou Bioenergy Hailun Co., Ltd.
[0069] Example 1: A method for preparing lignin-based porous carbon
[0070] The specific implementation includes the following steps:
[0071] The enzymatically hydrolyzed lignin, potassium carbonate and potassium dihydrogen citrate were ground and mixed in a mass ratio of 1:2.625:0.375, and then put into a tube furnace. Nitrogen protective gas was introduced at a rate of 100 mL / min, and the temperature in the tube furnace was increased to 700°C at a rate of 5°C / min. The mixture was carbonized at 700°C for 2 h, and then naturally cooled to 50°C before being taken out. The carbonized product was first washed with 1M HCl to remove all inorganic salts, and then washed with excess deionized water until the pH was 7, and filtered. Finally, the filter residue was placed in an oven and dried at 100°C for 12 h to obtain lignin-based porous carbon.
[0072] The prepared lignin-based porous carbon was analyzed by scanning electron microscopy ( Figure 1 ), it can be seen that the porous carbon is honeycomb-shaped and has a structure in which large, medium and small pores are interconnected. Such a channel structure is conducive to the transmission of ions.
[0073] 1. Specific surface area, pore size distribution and carbon yield
[0074] The prepared lignin-based porous carbon was subjected to surface area and pore size analysis tests ( Figure 2 ), the results show that the specific surface area of lignin-based porous carbon is 945m 2 / g, average particle size 2.59nm, total pore volume 0.869cm 3 / g; carbon yield 40%.
[0075] 2. Three-electrode electrochemical performance test
[0076] The prepared lignin-based porous carbon was made into electrode sheets, and the three-electrode electrochemical performance test was carried out ( Figure 3 ), the results are as follows: when the electrolyte is 6M KOH, at a current density of 1A / g, the material mass specific capacitance is 310F / g.
[0077] 3. Two-electrode electrochemical performance test
[0078] The prepared lignin-based porous carbon was prepared into electrode sheets and further assembled into capacitors for two-electrode electrochemical tests ( Figure 4 ), the results: after 10,000 cycles of charge and discharge at 5A / g, the specific capacitance of the capacitor decays less, the capacitance retention rate is as high as 99.5%, and the coulombic efficiency is close to 100%. It is calculated that the energy density of the device is 12.8Wh / kg at a power density of 2.78KW / kg.
[0079] Example 2: A method for preparing lignin-based porous carbon
[0080] The specific implementation method is the same as Example 1, except that the mass ratios of enzymatic lignin, potassium carbonate and potassium dihydrogen citrate are adjusted to 1:1.75:0.25, 1:3.5:0.5 and 1:4.375:0.625, and other conditions remain unchanged to prepare lignin-based porous carbon.
[0081] The lignin-based porous carbons prepared by three different mass ratios of enzymatic lignin, potassium carbonate and potassium dihydrogen citrate were analyzed by scanning electron microscopy. The results are as follows:
[0082] When the mass ratio of enzymatic lignin, potassium carbonate and potassium dihydrogen citrate is 1:1.75:0.25, the pore structure is small and the pores are not obvious. As the proportion of the activator increases, the degree of activation gradually increases, resulting in a larger and larger pore structure.
[0083] 1. Specific surface area, pore size distribution and carbon yield
[0084] The prepared lignin-based porous carbon was subjected to specific surface area and pore size analysis tests ( Figure 2 ), and calculated the carbon yield, the results are shown in Table 1:
[0085] Table 1
[0086]
[0087] 2. Three-electrode electrochemical performance test
[0088] After the porous carbon was prepared into electrode sheets, the three-electrode electrochemical performance test was carried out ( Figure 3 ), when the electrolyte is 6MKOH and the current density is 1A / g, the mass specific capacitance results of different electrode sheets are shown in Table 2:
[0089] Table 2
[0090]
[0091] Example 3: Optimization of reaction conditions for preparing lignin-based porous carbon
[0092] Specific implementation method The mass ratio of enzymatic lignin, potassium carbonate and potassium dihydrogen citrate is 1:3.5:0.5 as in Example 2, except that the carbonization temperature is adjusted to 600°C, 700°C, 800°C and 900°C to prepare lignin-based porous carbon.
[0093] 1. Specific surface area, pore size distribution and carbon yield
[0094] The prepared lignin-based porous carbon was subjected to specific surface area and pore size analysis and the carbon yield was calculated. The results are shown in Table 3:
[0095] Table 3
[0096]
[0097] 2. Three-electrode electrochemical performance test
[0098] After the porous carbon was prepared into electrode sheets, the three-electrode electrochemical performance test was carried out ( Figure 5 ), when the electrolyte is 6MKOH and the current density is 1A / g, the mass specific capacitance results of different electrode sheets are shown in Table 4:
[0099] Table 4
[0100]
[0101] It can be seen that with the increase of carbonization temperature, the specific capacitance of the porous carbon electrode shows a trend of first increasing and then decreasing, reaching a maximum value of 255F / g at a carbonization temperature of 700°C. Therefore, it is concluded that in this system, the carbonization temperature of 700°C is the optimal temperature.
[0102] Comparative Example 1: Preparation of lignin-based porous carbon using different potassium compounds and potassium carbonate as two activators
[0103] The specific implementation method is the same as Example 1, except that potassium dihydrogen citrate is replaced by potassium citrate and potassium hydroxide as activators, and the mass ratio of enzymatic lignin and the two activators and the carbonization temperature are adjusted accordingly to prepare lignin-based porous carbon.
[0104] After the porous carbon was prepared into an electrode sheet, a three-electrode electrochemical performance test was performed. When the electrolyte was 6M KOH and the current density was 1A / g, the mass specific capacitance results of different electrode sheets and the calculated carbon yield were shown in Table 5:
[0105] Table 5
[0106]
[0107] It can be seen that the electrochemical performance of the prepared lignin-based porous carbon three-electrode is not ideal.
[0108] Comparative Example 2: Preparation of lignin-based porous carbon using non-potassium compounds and potassium carbonate as two activators
[0109] Specific implementation method is the same as Example 1, except that potassium dihydrogen citrate is replaced by zinc chloride as the activator, and the mass ratio of enzymatic lignin and the two activators is adjusted accordingly to prepare lignin-based porous carbon.
[0110] After the porous carbon was prepared into an electrode sheet, a three-electrode electrochemical performance test was performed. When the electrolyte was 6M KOH and the current density was 1A / g, the mass specific capacitance results of different electrode sheets and the calculated carbon yield were shown in Table 6:
[0111] Table 6
[0112]
[0113]
[0114] It can be seen that when zinc chloride and potassium carbonate are used as composite activators, the maximum value of specific capacitance reached is about 200 F / g, which is not ideal. In addition, due to the high-intensity etching effect of zinc chloride, the carbon yield decreases significantly.
[0115] Comparative Example 3: Preparation of lignin-based porous carbon using different mass ratios of enzymatic lignin, potassium carbonate, and potassium dihydrogen citrate
[0116] The specific implementation method is the same as Example 1, except that the mass ratio of enzymatic lignin, potassium carbonate and potassium dihydrogen citrate is adjusted to 1:1.5:0.5, 1:2.5:0.5 and 1:4:0 to prepare lignin-based porous carbon.
[0117] After the porous carbon was prepared into an electrode sheet, a three-electrode electrochemical performance test was performed. When the electrolyte was 6M KOH and the current density was 1A / g, the mass specific capacitance results of different electrode sheets and the calculated carbon yield were shown in Table 7:
[0118] Table 7
[0119]
[0120] It can be seen that the three-electrode electrochemical performance of the porous carbon obtained by carbonization by adjusting these three mass ratios was not improved.
[0121] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing lignin-based porous carbon, characterized in that: The preparation method comprises the following steps: mixing enzymatically hydrolyzed lignin, potassium carbonate and potassium dihydrogen citrate in a mass ratio of 1:(1.75-4.375):(0.25-0.625), carbonizing, cooling, washing and drying to obtain lignin-based porous carbon.
2. The preparation method according to claim 1, characterized in that The mass ratio of the enzymatically hydrolyzed lignin, potassium carbonate and potassium dihydrogen citrate is preferably 1:(1.75-3.5):(0.25-0.5).
3. The preparation method according to claim 1, characterized in that The mass ratio of the enzymatically hydrolyzed lignin, potassium carbonate and potassium dihydrogen citrate is 1:2.625:0.
375.
4. The preparation method according to claim 1, characterized in that The carbonization temperature is 600-900°C, preferably 600-700°C.
5. The preparation method according to claim 1, characterized in that The steps include: Enzymatically hydrolyzed lignin, potassium carbonate and potassium dihydrogen citrate are mixed in a mass ratio of 1:(1.75-4.375):(0.25-0.625), carbonized at 600-900° C. for 1-3 hours, and then taken out after cooling to below 60° C., washed and dried to obtain lignin-based porous carbon.
6. Lignin-based porous carbon prepared by the preparation method according to any one of claims 1 to 5.
7. A method for improving the specific surface area, pore size distribution, carbon yield and electrochemical performance of lignin-based porous carbon, characterized in that: The method comprises the steps of mixing enzymatically hydrolyzed lignin, potassium carbonate and potassium dihydrogen citrate in a mass ratio of 1:(1.75-4.375):(0.25-0.625), carbonizing, cooling, washing and drying to obtain lignin-based porous carbon.
8. The method according to claim 7, characterized in that The steps include: Enzymatically hydrolyzed lignin, potassium carbonate and potassium dihydrogen citrate are mixed in a mass ratio of 1:(1.75-4.375):(0.25-0.625), carbonized at 600-900° C. for 1-3 hours, and then taken out after cooling to below 60° C., washed and dried to obtain lignin-based porous carbon.
9. Use of the lignin-based porous carbon according to claim 6 or the method according to claim 7 or 8 in preparing a working electrode.
10. Use of the lignin-based porous carbon according to claim 6 or the method according to claim 7 or 8 in preparing a supercapacitor.
Citation Information
Patent Citations
A porous carbon material for alkali lignin-based supercapacitors, its preparation method and application
CN106744793B
Graded porous carbon nanosheet for electrochemical application and preparation method
CN108328601A
Preparation method of biomass-based porous carbon and product
CN109879281A
Method for preparing mesopore-enriched graded porous carbon material for supercapacitor
CN110862077A
Lignin carbon-transition metal oxide asymmetric supercapacitor and preparation and application thereof
CN114512349A
Cited By
Petroleum asphalt-based composite porous carbon, preparation method thereof and supercapacitor
CN122158346A